Boys to Men in the Shadow of AIDS - Simpson, A. author. aut Link
VII, 243 p.
Keywords: This ethnography charts the lives of mission-educated men in Zambia and their search for meaning in the AIDS pandemic, as well as their responses to prevention and HIV testing. It also suggests how hegemonic masculinities may begin to be re-figured and gender relationships redesigned.